Integrative Review of Recruitment of Research Participants Through Facebook - Reagan, Louise; Nowlin, Sarah Y; Birdsall, Stacia B; Gabbay, Juliana; Vorderstrasse, Allison; Johnson, Constance; D'Eramo Melkus, Gail (Nursing research (New York), 2019)
Facebook (FB) has been widely used recently to recruit participants for adult health research. However, little is known about its effectiveness, cost, and the characteristics of participants recruited via FB when compared to other recruitment methods. The purpose of this integrative review was to examine the published evidence concerning the use of FB in participant recruitment for adult health research, as compared to other social media, online, and traditional recruitment methods. In this integrative review, we used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. PubMed, CINAHL, SCOPUS, and Web of Science were the electronic databases used to identify the published articles. In regard to language, the search was limited. The efficacy and cost-effectiveness of using FB for recruitment in healthcare research as compared to more traditional forms of recruitment remain unclear. Reporting of recruitment strategies is inconsistent, and costs are often not included. FB is being used for recruitment frequently with other methods and, although often effective, can be costly. FB is used to recruit participants for a variety of studies, with researchers using both free and paid ads to reach potential participants. Reporting of recruitment methods needs to be more rigorous, streamlined, and standardized in scientific papers.